1997
DOI: 10.1093/carcin/18.6.1225
|View full text |Cite
|
Sign up to set email alerts
|

Acinar differentiation by non-malignant immortalized human prostatic epithelial cells and its loss by malignant cells

Abstract: Invasive prostatic carcinomas and prostatic intraepithelial neoplasia (PIN) are characterized by a loss of normal cell organization, cell polarity, and cell:cell and cell:basement membrane adhesion. The objective of this study was to establish in vitro three-dimensional (3-D) cell models which can be used to investigate mechanisms involved in acinar morphogenesis and differentiation in normal prostatic epithelium and their abnormalities in cancer cells. The process of acinar morphogenesis, including structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 10 publications
7
90
0
Order By: Relevance
“…These interactions involve insoluble extracellular matrix, stroma consisting of fibroblast, adipose, vasculature, and resident immune cells as well as the conventional milieu of cytokines and growth factors (18). As a result of an alteration in these interactions, changes in the tissue organization are observed in many epithelial cancers including invasive prostatic carcinomas (19). The ability to form acinar structure was shown for low tumorigenic breast epithelial cells, whereas more malignant cells grew as chaotic clusters.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions involve insoluble extracellular matrix, stroma consisting of fibroblast, adipose, vasculature, and resident immune cells as well as the conventional milieu of cytokines and growth factors (18). As a result of an alteration in these interactions, changes in the tissue organization are observed in many epithelial cancers including invasive prostatic carcinomas (19). The ability to form acinar structure was shown for low tumorigenic breast epithelial cells, whereas more malignant cells grew as chaotic clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The non-cancerous cells were characterized by formation of acini (cell clusters), which resemble in vivo structures of prostate epithelial cells. Cancer prostate cells showed lack of organization and increased invasiveness, which is associated with cancer aggressiveness (Webber et al 1997). Matrigel constituent proteins promote cell-matrix interactions, affecting cell proliferation and differentiation.…”
Section: Multicellular Tumour Spheroids As a Primary 3d Tumour Modelmentioning
confidence: 99%
“…Assays developed to measure neural and mammary stem cell self-renewal in vitro propagate these cells as spheres in an attempt to preserve their specialized biology (23,24). Several studies have shown that human prostate cells can form epithelial spheroids when cocultured with stromal cells and suspended in Matrigel in vitro (25)(26)(27). This strategy was adapted to develop a method for measuring murine prostate stem cell self-renewal.…”
Section: The Lsc Subpopulation Is Enriched For Sphere-forming Cells Withmentioning
confidence: 99%